What do Asian Countries Want the Seat at the High Table for? G20 as a New Global Economic Governance Forum and the Role of Asia - Yoon Je Cho (Asian Development Bank (ADB), 2011)
The recent global crisis has reminded everyone of the importance of reforming the international monetary and financial system. The current system is no longer adequate to meet the needs of a complex, integrated world economy. Various proposals, both on the demand and supply sides, have been put forward, and include building a stronger global financial safety net, diversifying the supply of international reserve currencies, and so on. However, these proposals face trade-offs between desirability and political feasibility. > In this situation, a practical proposal entails strengthening policy coordination among the major economies and reforming the International Monetary Fund. Success on both fronts depends heavily on reform of global economic governance and the effectiveness of the G20. Asia`s representation in the G20, and its increased status, give both privileges and responsibilities. To meet these responsibilities, Asians should invest greater efforts in developing their intellectual leadership in global economic issues.
hdl:11540/2291
Keywords: F42; F53; F55; 330; Global Economic Governance Reform; Reform of International Monetary System; Reform of the International Monetary Fund; The role of Asia in global economic governance